2018
DOI: 10.2147/jpr.s172235
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative use of methadone improves control of postoperative pain in morbidly obese patients: a randomized controlled study

Abstract: ObjectivesSurgical patients still commonly experience postoperative pain. With the increasing prevalence of obesity, there is a growing demand for surgical procedures by this population. Intraoperative use of methadone has not been well assessed in this population.Materials and methodsPatients with a body mass index of 35 kg/m2 or more undergoing bariatric surgery were randomly assigned to receive either fentanyl (group F) or methadone (group M) in anesthesia induction and maintenance. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…These findings are in accordance with results published by Machado et al. [14], who showed a significant reduction in rescue morphine use up to 48 h in patients who received methadone after open bariatric surgery, when compared with intra‐operative fentanyl. Our results are also in line with a published meta‐analysis of 13 clinical trials that showed that intra‐operative methadone reduced consumption of opioids up to 72 h after surgery [27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in accordance with results published by Machado et al. [14], who showed a significant reduction in rescue morphine use up to 48 h in patients who received methadone after open bariatric surgery, when compared with intra‐operative fentanyl. Our results are also in line with a published meta‐analysis of 13 clinical trials that showed that intra‐operative methadone reduced consumption of opioids up to 72 h after surgery [27].…”
Section: Discussionsupporting
confidence: 92%
“…[28], which provides more trustworthy data on the pain felt by patients in the period immediately after surgery than pain scores assessed at fixed times. Other authors have also observed lower pain scores early on in PACU for patients who received methadone after open bariatric surgery, compared with fentanyl [14] and in spinal surgery, compared with hydromorphone [16]. Furthermore, Machado et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both drugs had considerable effects when used intramuscularly, intravenously and intraarticular to relieve postoperative pain (9)(10)(11)(12). Tramadol could also reduce pain when used subcutaneously around the wound alone or in combination with ketamine (8).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, at 3 months after operation, patients who received methadone also tended to have less evoked pain at the surgical scar. 23 In a dose escalation study in an ambulatory-surgery population, patients received a single dose of i.v. methadone or a variety of other opioids.…”
mentioning
confidence: 99%